EFFECTS OF GLOBAL FINANCIAL CRISES ON THE ECONOMY AND ANTI-CRISIS MEASURES (European Journal of Interdisciplinary Research and Development, 2024)
Global financial crises (GFCs) have significant and far-reaching effects on the global economy, including recessions, rising unemployment, loss of wealth, and instability in financial markets. These crises lead to contractions in GDP, disruptions in business activities, and an increased risk of bank failures. In response, governments and central banks implement a variety of anti-crisis measures, including monetary interventions like interest rate cuts and quantitative easing, fiscal stimulus packages, and regulatory reforms aimed at strengthening the financial system. Despite these measures, the recovery from a financial crisis is often slow and uneven, with long-term challenges such as high public debt, rising inequality, and structural economic shifts. This paper explores the impacts of global financial crises on economic stability and the effectiveness of anti-crisis policies, with a focus on the 2008 crisis as a case study.